DEMOCRATIC THINKING AND CIVIC EDUCATION IN GREECE: AN ORDINAL LOGISTIC REGRESSION MODEL - Anthony Papaoikonomou (İmgelem)
This paper presents a research that was carried out in autumn of 2021in Thessaloniki, Greece. Main purpose was to find out the link between democratic behavior of Greek young adults and the civic education that is obtained in public secondary education. For this reason, 524 students of the department of political sciences were asked questions regarding their points of view on civic education in public schools. This sample was chosen due to the political sensitization they have, because of their main field of studies. The results showed the emphasis they pose on public schools as far as the political education is concerned. Moreover, views that politicization is connected with peer groups and watching TV were refuted.Keywords: Democratic Behavior, Greek Educational System, Secondary Education, Civic Education, Students, Ordinal Regression.